Nanostructuring of Rare‐earth‐based Single‐Molecule Magnets as Long‐range Ordered Arrays in the Framework of Organic Metal Halide Perovskites. (3rd March 2023) - Chai, Congcong; Zhou, Junyan; Hao, Munan; Li, Qi; Lu, Jiali; Jin, Shifeng; Chen, Xiaolong
Abstract: The nanostructuring of single‐molecule magnets (SMMs) on substrates, in nanotubes and periodic frameworks is highly desired for the future magnetic recording devices. However, the ability to organize SMMs into long‐range ordered arrays in these systems is still lacking. Here, we report the incorporation of magnetic (RECl2 (H2 O)6 ) + (RE=rare earths) molecular groups into the framework of an organic metal halide perovskite (OMHP)—(H2 dabco)CsCl3 . Intriguingly, we show the incorporated rare‐earth groups self‐organized into long‐range ordered arrays that uniformly and periodically distributed in the A sites of OMHP. The ordered (RECl2 (H2 O)6 ) + groups serve as SMMs in the perovskite frameworks, exhibiting large effective magnetic moment, moderate magnetic anisotropy and two‐step relaxation behavior. With the additional merit of great structural flexibility and multifunction of OMHPs, the preparation of the first SMMs@OMHP magnetic materials furthers the development of molecular spintronics. Abstract : The first compound with long‐range ordered single‐molecule magnets (SMMs) encapsulated in protective framework was synthesized and its structure and magnetic properties were investigated. This work provides a method to control the nanostructuring of SMM within protective frameworks and further the development of molecular spintronics.